VEGF mRNA Expression in Epithelial Ovarian Cancer: Correlation with rs699947 Gene Variant - Prameswari, Yuda Nabella; Suryandari, Dwi Anita; Sukmawati, Dewi; Yunaini, Luluk; Kodariah, Ria (Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Angiogenesis is the formation of new blood vessels, is crucial for cancer growth and metastasis, including in epithelial ovarian cancer (EOC). Vascular Endothelial Growth Factor (VEGF) regulates angiogenesis, and its elevated mRNA expression is linked to poor prognosis in cancer. Genetic variations, such as the rs699947 polymorphism in the VEGF gene, can affect VEGF expression and contribute to cancer progression.Objective: The primary aim of this study is to examine the distribution of the VEGF rs699947 polymorphism and its correlation with VEGF mRNA expression levels in patients with low-grade and high-grade EOC at Dr. Cipto Mangunkusumo Hospital, Indonesia.Methods: This research is a cross-sectional analysis involving 65 normal female whole blood samples and a total of 80 ovarian cancer biopsy samples, including 15 ovarian cysts as expression calibrators, along with 36 low-grade and 29 high-grade EOC samples. The distribution of genotypes and alleles of the VEGF rs699947 polymorphism was assessed through ARMS PCR analysis, while VEGF mRNA expression was quantified using real-time qPCR.Results: Significant differences were observed in both genotype (p<0,01) and allele (p=0,000) distributions between the normal and cases group. The relative mRNA expression of VEGF was significantly elevated in both low-grade and high-grade EOC. Individuals with the homozygous VEGF rs699947 AA genotype exhibited the highest mRNA expression compared to other genotypes. In contrast, individuals carrying the CC genotype showed the lowest correlation with VEGF mRNA expression in both low-grade and high-grade EOC.Conclusion: This study shows that the A allele of VEGF rs699947 is correlated with increased VEGF mRNA expression in EOC patients, particularly in those with the AA genotype. Conversely, the C allele may offer a protective effect against EOC, as the CC genotype is linked to lower VEGF mRNA expression. Genetic screening for VEGF rs699947 could facilitate early detection and inform targeted therapeutic strategies.